High Rate of Revision Surgery After Limited Decompression of Lumbar Facet Cysts. Issue 21 (1st November 2022) - Thompson, Kirk; Rhyne, Alfred; Johnson, Nicholas; Stokman, Jim; Darden, Bruce; Milam, Alden; Laxer, Eric; Spector, Leo; Segebarth, Brad; Chapman, Todd M.
Abstract : Introduction: The surgical treatment of lumbar facet cysts has long been debated. Some surgeons elect for limited decompression of such cysts while other surgeons elect for primary decompression and fusion over concerns for recurrence and instability. Previous studies have suggested the rate of revision surgery after facet cyst excision to be as low as 1%, whereas others have reported this rate to be markedly higher. In this study, we examined revision surgery rates and patient-reported outcomes and conducted a radiographic analysis to identify predictors of failure after limited decompression of lumbar facet cysts. Methods: A retrospective review of the electronic medical records of patients treated at our institution using the Current Procedural Terminology code 63267 before January 2018 was conducted. The primary outcome measure was revision surgery at the index level for recurrence or instability or a minimum 2-year follow-up without revision surgery. Secondary outcome measures include radiographic assessments of preoperative and postoperative spondylolisthesis and patient-reported outcome measures. Using preoperative MRI studies, an analysis of facet angles at the surgical level was conducted and the presence, location, and amount of facet fluid were calculated. Results: A total of 162 patients met inclusion criteria. Of these, 93 patients had a minimum 2-year follow-up. Of these, 19 had undergone a revision surgery at the index level for cyst recurrence or instability. The revision rate for this group was 20.4%. The median time to initial revision surgery was 2.2 years. The median time from index operation to last follow-up was 3.8 years. No differences were observed between the groups regarding the presence of preoperative spondylolisthesis, age, sex, body mass index, blood loss, or patient demographics. 60.2% of all procedures were done at the L4-5 level, but this level accounted for 73.7% of primary failures. A radiographic analysis showed facet angle >45° at L4-5 to be associated with risk of failure of primary decompression. The presence and absolute amount of fluid in the facets were not associated with risk of failure at the L4-5 level. Discussion: Our revision rate of 20.4% is higher than what is commonly reported in the literature. The radiographic analysis shows that at the L4-5 level, a facet angle of >45° is associated with failure of primary decompression.